East West German wage convergence - How far have we got? - Viktor Steiner; Kersten Wagner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1997)
At the start of the German unification process it was a commonly held view that east German living conditions will converge to west Geman levels within a few years. This view was not only held by notoriously optimistic politicians but also by a great many of professional economists. With hindsight, this optimism turned out as unfounded. Although living standards have improved substantially for the great majority of east Germans, this is more related to the huge west German transfers than productivity improvements of the east German economy. For political reasons, wage increases stipulated in collective bargaining agreements were detached from economic factors, which the majority of economists considers the main culprit for the dramatic decline in employment and the unprecedented increase in unemployment in the east German economy.
Keywords: 330; Regionale Lohnstruktur; Wirtschaftliche Anpassung; Humankapital; Sektorale Beschäftigungsstruktur; Betriebsgröße; Deutschland; Neue Bundesländer